Extraction of protein concentrate from red bean (Phaseolus vulgaris L.): antioxidant activity and inhibition of lipid peroxidation - Piñuel, María Lucrecia (2019)
Fil: Piñuel, María L. Universidad Nacional de Río Negro; Argentina